Consideraciones en redacción científica: discusión, conclusiones y referencias - Castro-Rodríguez, Yuri (2018)
The discussion section is responsible for interpreting and analyzing the results of a study, as well as presenting the practical/clinical implications of the findings, the limitations of the study and recommendations for future studies aimed to improve the original research. As the different segments of a scientific article, the discussion, conclusions and references follow standardized rules of scientific writing and publication that should be known by the authors. These rules will give the author the opportunity to facilitate and expedite the process of preparation and publishing. In the other hand, the reader will be able to understand, in a simple way, the data found in the study. This scientific note summarizes the main recommendations and guidelines for properly writing the discussion, conclusions and references of a scientific article.